2009
DOI: 10.1159/000252976
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Efficacy of Toothpaste Containing Casein Phosphopeptide in the Prevention of Dental Caries: a Randomized Controlled Trial in 12- to 15-Year-Old High Caries Risk Children in Bangalore, India

Abstract: Casein phosphopeptide (CPP) has the potential to be added to mouth rinses, gels, toothpastes, chewing gums and confectioneries. Until now CPP has been studied in vitro, in situ and in animals, but clinical trials are lacking. This study was conducted to evaluate the efficacy of CPP-containing toothpaste in preventing dental caries in schoolchildren. The study was conducted among 150 schoolchildren randomly divided into three groups, each using one of three types of toothpastes: (a) containing 2% w/w CPP; (b) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
44
1
11

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 26 publications
0
44
1
11
Order By: Relevance
“…For this reason, the effects of dentifrices on dental erosion have been exhaustively studied (12,(22)(23)(24). While some studies have shown that products with bioactive agents such as fluoride, CPP-ACP, and calcium sodium phosphosilicate have the potential to prevent enamel demineralization (20,23,24), other studies have shown no favorable effects of these agents (12,22). @ C I C E d i z i o n i I n t e r n a z i o n a l i…”
Section: @ C I C E D I Z I O N I I N T E R N a Z I O N A L Imentioning
confidence: 99%
“…For this reason, the effects of dentifrices on dental erosion have been exhaustively studied (12,(22)(23)(24). While some studies have shown that products with bioactive agents such as fluoride, CPP-ACP, and calcium sodium phosphosilicate have the potential to prevent enamel demineralization (20,23,24), other studies have shown no favorable effects of these agents (12,22). @ C I C E d i z i o n i I n t e r n a z i o n a l i…”
Section: @ C I C E D I Z I O N I I N T E R N a Z I O N A L Imentioning
confidence: 99%
“…As stated above, many published in situ studies on the CPP-ACP technology have demonstrated a significant remineralization of enamel subsurface lesions predicting a slowing of caries progression and promotion of lesion regression in an RCT. This prediction has now been validated in 4 published RCTs [Andersson et al, 2007;Morgan et al, 2008;Bailey et al, 2009;Rao et al, 2009]. One RCT demonstrated that CPP-ACP in a sugar-free chewing gum, relative to a normal sugar-free gum, significantly slowed progression and enhanced regression of approximal caries in a population of schoolchildren .…”
mentioning
confidence: 92%
“…One RCT demonstrated that CPP-ACP in a sugar-free chewing gum, relative to a normal sugar-free gum, significantly slowed progression and enhanced regression of approximal caries in a population of schoolchildren . Another 2 RCTs demonstrated that CPP-ACP delivered in a tooth cream significantly regressed white-spot lesions in postorthodontic populations [Andersson et al, 2007;Bailey et al, 2009], and recently another RCT showed that CPP and calcium carbonate in a toothpaste formulation, which would spontaneously form CPP-ACP in saliva, significantly reduced caries experience in children compared with a placebo toothpaste [Rao et al, 2009].…”
mentioning
confidence: 99%
“…Recently, CPP (without the addition of ACP) has been shown to reduce caries incidence in a clinical trial [Rao et al, 2009].…”
mentioning
confidence: 99%